Social Media Ethics and Digital Footprint Education for Students of PGRI 2 Patrang Middle School, Jember Regency - Juhanda; Dodik Aris Setiawan (Universitas Muhammadiyah Jember, 2025)
The community service activity entitled Social Media Ethics and Digital Footprint Education was conducted at PGRI 2 Patrang Junior High School, Jember Regency, to enhance students’ digital literacy and ethical awareness. This program addressed the increasing social media use among adolescents without sufficient understanding of digital ethics and responsibility. The activity employed a two-day seminar and interactive training approach, covering topics such as social media ethics, data privacy, and digital footprint management. The results indicated an improvement in students’ understanding from 58% to 87% based on pre-test and post-test scores. Participants demonstrated high enthusiasm and positive feedback. The program effectively fostered digital ethical awareness, critical thinking about online information, and responsible social media behavior. It is expected to serve as a sustainable educational model for schools to develop digital character among young learners